Specific Features of Construction of Thawed Soil Dams in Severe Climate Conditions (Osovennosti Stroitelstva Talkh Plotin Iz Gruntovkh Materialov v Usloviykh Surovogo Klimata) - Biianov,G F; Kudoyarov,L I (1977)
Thawed dams, which allow thawing of frozen soils in the foundation during operation, can be built provided the deformations in the foundation due to thawing and thermal settling do not result in a loss of the stability of the structure. Development and implementation of a set of measures will make it possible to build dams out of binding soils in the Far North at temperatures down to -40 to -45 deg C and to eliminate completely the seasonal nature of construction work. The dumping of excess water during construction over the crest of an uncompleted dam will make it possible to reduce the cost of building expensive temporary water diversion structures. (Author) Trans. from Soviet-American Working Seminar Technology of Construction of Structures under Cold-Climate Conditions (USSR) N. P. 16-28 May 77.